Solution :
To Prove :-
- tan⁴ θ + tan² θ = sec⁴ θ - sec²θ
Proof :-
So here we would be proving the L.H.S. equal to R.H.S.,
⇒ tan⁴ θ + tan² θ
Taking tan² θ as common,
⇒ tan² θ (tan² θ + 1)
Identity as we know that,
By using it we gets,
⇒ tan² θ (sec² θ)
Now putting sec²θ - 1 in the place of tan²θ,
⇒ (sec²θ - 1) (sec² θ)
⇒ (sec²θ - 1) × (sec² θ)
⇒ sec⁴θ - sec² θ
Hence proved..!!!
Additional Information :
- sin² θ + cos² θ = 1
- sin² θ = 1 - cos²θ
- sec²θ = 1 + tan²θ
- cot²θ = cosec²θ - 1
Reciprocal identities :-
- sin θ = 1 / cosecθ
- cosec θ = 1 / sin θ
- cos θ = 1 / sec θ
- sec θ = 1 / cos θ
- tan θ = 1 / cot θ
- cot θ = 1 / tan θ